Avaliação da capacidade antioxidante do extrato de guavira (Campomanesia sp.) - Felipe de Almeida Machado, Luís; Carolina Alves Gomes , Ana; Mendes Oliveira , Dalton; Serenato Madalozzo , Elisângela (ANAIS DO ENIC, 2026)
-